The HELPERS Model: A new management model of festival volunteering. - Holmes, Kirsten; Lockstone-Binney, L.; Rixon-Booth, A.; Smith, K. (Routledge, 2018)
It then goes on to explore and detail a new volunteer management model for recruiting and managing volunteer programmes across a range of festivals and events developed by the Australian company I Need Helpers (INH). The model in  ...